Irony and Lexical Creativity during the Coronavirus Pandemic - Rodríguez González, Félix (2022)
The purpose of this article is to examine some of the sudden changes that have recently taken place in the European Spanish lexis, especially in times of the coronavirus pandemic. Due to the strong feelings that arose during the lockdown period, the linguistic processes registered have a marked emotional character and a political tinge, and respond to semantic and morphological motivations. On the one hand, usual resources in political rhetoric stand out, such as euphemism and, above all, dysphemism, which by metaphorical means tends towards irony and humor. From the morphological angle, the same end, blends and lexical creations based on acronyms stand out.